2013
DOI: 10.1055/s-0033-1355865
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Cardiac Tissue Doppler and Peripheral Vascular Doppler in the Anemic Fetus – An Additional Method to Determine the Transfusion Threshold?

Abstract: In fetal anemia, peak systolic myocardial TDI parameters correlate with vascular Doppler parameters, confirming that TDI is a promising method to evaluate myocardial function in the anemic fetus. This suggests combining both techniques to quantify fetal myocardial function in anemia even more accurately, possibly allowing for the determination of the indication for intrauterine transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Only a few studies have focused on how the myocardium and the pump function of the fetal heart is affected during anemia and IUT. Michel et al showed an increase in peak systolic myocardial strain in anemic fetuses that partially normalized after IUT [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have focused on how the myocardium and the pump function of the fetal heart is affected during anemia and IUT. Michel et al showed an increase in peak systolic myocardial strain in anemic fetuses that partially normalized after IUT [10,11].…”
Section: Introductionmentioning
confidence: 99%